Identification of Antihypertensive Peptides Derived from Low Molecular Weight Casein Hydrolysates Generated during Fermentation by Bifidobacterium longum KACC 91563 - Ha, Go Eun (Korean J Food Sci Anim Resour, 2015)
Angiotensin-converting enzyme (ACE) inhibitory activity was evaluated for the low-molecular-weight fraction (<3 kDa) obtained from milk fermentation by Bifidobacterium longum KACC91563. The ACE inhibitory activity in this fraction was 62.3%. The peptides generated from the <3 kDa fraction were identified by liquid chromatography-electrospray ionization quantitative time-of-flight mass spectrometry analysis. Of the 28 peptides identified, 11 and 16 were identified as β-casein (CN) and α(s1)-CN, respectively. One peptide was identified as κ-CN. Three peptides, YQEPVLGPVRGPFPIIV, QEPVLGPVRGPFPIIV, and GPVRGPFPIIV, from β-CN corresponded to known antihypertensive peptides. We also found 15 peptides that were identified as potential antihypertensive peptides because they included a known antihypertensive peptide fragment. These peptides were as follows: RELEELNVPGEIVE (f1-14), YQEPVLGPVRGPFP (f193-206), EPVLGPVRGPFPIIV (f195-206), PVLGPVRGPFPIIV (f196-206), VLGPVRGPFPIIV (f197-206), and LGPVRGPFPIIV (f198-206) for β-CN; and APSFSDIPNPIGSENSEKTTMPLW (f176-199), SFSDIPNPIGSENSEKT- TMPLW (f178-199), FSDIPNPIGSENSEKTTMPLW (f179-199), SDIPNPIGSENSEKTTMPLW (f180-199), DIPNPIGSENSEKTTMPLW (f181-199), IPNPIGSENSEKTTMPLW (f182-199), PIGSENSEKTTMPLW (f185-199), IGSENSEKTTMPLW (f186-199), and SENSEKTTMPLW (f188-199) for α(s1)-CN. From these results, B. longum could be used as a starter culture in combination with other lactic acid bacteria in the dairy industry, and/or these peptides could be used in functional food manufacturing as additives for the development of a product with beneficial effects for human health.